Pengurusan Perubahan Pendidikan : Pelaksanaan Kurikulum Sains Sekolah Rendah - Zakiah, Mor (1999)
The purpose of this research was to study the effectiveness of the Primary School Science Curriculum or Kurikulum Sains Sekolah Rendah (KSSR) which was implemented from the beginning of the 1994/1995 school session as replacement of the Kurikulum Alam dan Manusia. This exploratory descriptive study investigated the effectiveness of KSSR training programmes for science teachers, level of management on KSSR changes executed by the headmaster, attitude, acceptance and performance of headmasters and science teachers in the KSSR and problems faced on implementing the KSSR. This study also investigated whether there was any correlation between KSSR training programmes, management of KSSR changes and attitude, acceptance and performance of teachers in KSSR. The sample consisted of every headmaster and two science teachers in each of the 97 schools which were chosen from 134 schools in Seberang Perai using random selection method. Pilot test was done on questionnaires designed by the researcher and reliability on the questionnaires for the headmasters and the science teachers were high. The questionnaires for the headmasters consisted of six sections; background, management on KSSR changes, attitude towards KSSR, acceptance of KSSR and performance in KSSR. The questionnaires for the science teachers consisted of seven sections with the addition at KSSR training programmes section. Data was analyzed using descriptive statistical method and hypotheses testing were done using inferential statistical method and correlation analyses. KSSR training programmes and management of KSSR changes were found to be at the ‘satisfactory’ level. Attitude, acceptance and performance of teachers on KSSR as a whole was also at the ‘satisfactory’ level. Nevertheless, there was still a small percentage of science teachers who showed resistance with attitude, acceptance and performance at the ‘unsatisfactory’ level. The study also found that training programmes and management on KSSR changes showed significant relationship with attitude, acceptance and performance of teachers involved in the KSSR. Correlation testing on the headmasters showed that management on KSSR changes was influenced by their attitude, acceptance and performance. The performance of the headmasters in KSSR showed higher influence compared to their attitude and acceptance of KSSR.The study had identified 10 causes related to the problems in implementing KSSR. Since each of the causes was negligible in their percentage, the researcher regarded the problems were not serious. Based on the findings, it could be concluded that KSSR had been implemented almost successfully and had nearly achieved its expectation level.